Influence of rootstocks on budding success in Nagpur mandarin (Citrus reticulata Blanco.) under Hadoti region - Yadav, Aruna; Singh, J.; Jain, M.C.; Bhatnagar, P.; Dashora, L.K. (Indian Journal of Agroforestry, 2020)
An experiment was conducted during 2008-09 to observe budding success over different rootstocks of citrus species for raising plants of Nagpur Mandarin in Hadoti region of Rajasthan. It was found that maximum budding success (68.3%), minimum days (54.4) required for 50 % sprouting, maximum length of scion shoot (17.98 cm), maximum plant height (34.584 cm) and maximum number of nodes/plant (1.546) were there in scion budded on Rough lemon. From the experiment it appeared that Rough lemon showed vigorous effect on the scion of Nagpur Mandarin.